MTP Arthrodesis: Percutaneous Interfragmentary Screw Placement and Nerve Injury. Issue 1 (January 2022) - Andrews, Nicholas A.; Patch, David A.; Jacob, Roshan; Sutherland, Charles R.; Harrelson, Whitt; Agarwal, Abhinav; Shah, Ashish
Category: Basic Sciences/Biologics; Midfoot/Forefoot Introduction/Purpose: Iatrogenic cutaneous nerve injury is the most common complication encountered in foot and ankle surgery with limited evidence to inform surgeons on neuroprotective techniques. The purpose of this study was to assess risk for injury to the dorsomedial cutaneous nerve (DCN) during insertion of percutaneous interfragmentary screws used in metatarsophalangeal (MTP) arthrodesis. Methods: Ten mid-tibia fresh frozen cadaver specimens were obtained for execution of this study. All cadavers were grossly and radiographically inspected for any evidence of existing pathology or prior operative intervention. Percutaneous placement of interfragmentary screw in both distal to proximal and proximal to distal fashion was performed. Only the skin was incised before reaming and screw placement. After screw placement, dissection of the great toe was conducted. The distance between the screws and the DCN was obtained. The DCN was also inspected for injury. Results: A total of 10 cadavers were included. The average age of our population was 64 (+- 12.6). Males represented 80% of our included specimens. Injury to the DCN was not reported using the proximal to distal screw fixation. The mean distance from the dorsal cutaneous nerve using proximal to distal interfragmentary screw fixation was 7.45+- 3.85 mm compared to 4.30+-2.71 mm in the distal to proximal screw. Distal to proximal screw fixation was associated with 10% risk of nerve injury with no nerve injuries occurring at the site of proximal to distal screws. Conclusion: In our cadaver study, proximal to distal screw fixation seems to offer neuroprotection in the setting of MTP arthrodesis. The DCN is known to have many anatomic variants, and DCN injuries can be a pretext for painful neuroma formation. Surgeons should consider careful dissection to the joint capsule in effort to decrease the risk of neurogenic injury when placing interfragmentary screws in MTP arthrodesis.